Impaired Myocardial Function Is Prognostic for Severe Respiratory Failure in the Course of COVID-19 Infection - Petersen-Uribe, Alvaro; Avdiu, Alban; Martus, Peter; Witzel, Katja; Jaeger, Philippa; Zdanyte, Monika; Heinzmann, David; Tavlaki, Elli; Warm, Verena; Geisler, Tobias; Müller, Karin; Gawaz, Meinrad; et al. (Frontiers in Cardiovascular Medicine, 2021)
COVID-19 may lead to severe acute respiratory distress syndrome (ARDS) resulting in increased morbidity and mortality. Heart failure and/or pre-existing cardiovascular disease may correlate with poor outcomes and thus require special attention from treating physicians. The present study sought to investigate a possible impact of impaired myocardial function as well as myocardial distress markers on mortality or ARDS with need for mechanical ventilation in 157 consecutive patients with confirmed SARS-CoV-2 infection. All patients were admitted and treated at the University Hospital of Tübingen, Germany, during the first wave of the pandemic. Electrocardiography, echocardiography and routine blood sampling were performed at hospital admission. Impaired left-ventricular and right-ventricular function, tricuspid regurgitation > grade 1 and elevated RV-pressure as well as thrombotic and myocardial distress markers (D-dimers, NT-pro-BNP and troponin-I) were associated with mechanical ventilation and/or all-cause mortality. Impaired cardiac function is more frequent amidst ARDS leading to subsequent need for mechanical ventilation, and thus denotes a poor outcome in COVID-19. Since a causal treatment for SARS-CoV-2 infection is still lacking, guideline-compliant cardiovascular evaluation and treatment remains the best approach to improve outcomes in COVID-19 patients with cardiovascular comorbidities.